Mizoroki-Heck reaction of 1,2-disubstituted aryl alkenes: variables of synthesis, solvent and ligand modulation of reactivity - Bangar, Pronnoy G.; Jawalkar, Priyanka R.; Dumbre, Swapnil R.; Raut, Pallavi K.; Patil, Dharmaraj J.; Tv, Neethu; Sudhakaran, Shana; Iyer, Suresh (Synthetic Communications, 2020)
Reaction of aryl iodides with 1,2-disubstituted aryl alkenes in the presence of TBABr/TBACl gave high yields of the Mizoroki-Heck product. Phosphine ligands were used for the modulation of reactivity and stereoselectivity, for the reaction of 4-iodoanisole with cinnamaldehyde. tert-Bu3P.HBF(4)gave the highest E:Z ratio of 1:0.08. The use of PEG-200 and PEG-400 as solvent could activate the reaction of aryl iodides with various 1,2-disubstituetd aryl alkenes.
Keywords: 12-Disubstituted aryl alkenes; 400; ligand effect; Mizoroki-Heck reaction; PEG 200; TBABr